2023
DOI: 10.1021/acs.joc.3c01700
|View full text |Cite
|
Sign up to set email alerts
|

Metal- and Solvent-Free Synthesis of Substituted Pyrimidines via an NH4I-Promoted Three-Component Tandem Reaction

Fang Fang,
Jie Xia,
Siying Quan
et al.

Abstract: A facile and practical approach for the preparation of substituted pyrimidines from ketones, NH 4 OAc, and N,N-dimethylformamide dimethyl acetal has been described. This NH 4 I-promoted three-component tandem reaction affords a broad range of substituted pyrimidines in acceptable yields under metal-and solvent-free conditions. The present methodology features the advantages of simple and easily available starting materials, metaland solvent-free conditions, a broad substrate scope with good functional group to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Being able to effectively generate 1,6-dihydropyrimidines from 1,3-diazabicylco[3.1.0]hex-3-enes we wished to couple their oxidation to the corresponding pyrimidine products in a telescoped manner as such densely functionalised scaffolds are gaining momentum in the pharmaceutical and materials fields. [28][29][30][31][32] Moreover, we targeted the replacement of previously used oxidants such as DDQ, [10] a hazardous and non-environmentally friendly agent. Initial efforts considered the use of MnO 2 as a solid oxidant that could be packed into flow cartridges, however, it was found that a stronger oxidant was needed to obtain the desired pyrimidines in a fast and clean process.…”
Section: Synthesis Of 16-dihydropyridimines and Related Pyrimidinesmentioning
confidence: 99%
“…Being able to effectively generate 1,6-dihydropyrimidines from 1,3-diazabicylco[3.1.0]hex-3-enes we wished to couple their oxidation to the corresponding pyrimidine products in a telescoped manner as such densely functionalised scaffolds are gaining momentum in the pharmaceutical and materials fields. [28][29][30][31][32] Moreover, we targeted the replacement of previously used oxidants such as DDQ, [10] a hazardous and non-environmentally friendly agent. Initial efforts considered the use of MnO 2 as a solid oxidant that could be packed into flow cartridges, however, it was found that a stronger oxidant was needed to obtain the desired pyrimidines in a fast and clean process.…”
Section: Synthesis Of 16-dihydropyridimines and Related Pyrimidinesmentioning
confidence: 99%
“…Due to the wide distribution of pyrimidines in natural products and functional materials, and their remarkable biological and pharmacological significance, a variety of methods for the synthesis of these molecules have been reported over the past few decades. 13 To obtain 2- or 4-amino, and 2,4- or 4,6-diaminopyrimidines, which are privileged structures in drug development, preferred methods involved the amination of the corresponding 2,4(4,6)-dihalopyrimidines by direct substitution with primary and secondary amines via SNAr reactions. 14,15 Nevertheless, the preparation of these halopyrimidine precursors from simple building blocks often involves the use of hazardous reagents/catalysts and harsh reaction conditions, also requiring multistep procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, using ammonium salts as a nitrogen source, simple and effective approaches for constructing structurally diverse N-heterocycles have been reported. 12 In recent years, our group also successfully utilized ammonium salts as a nitrogen source for a facile construction of thiazoles, 13 quinazolines, 14 pyridines, 15 pyrimidines, 16 pyrroles, 17 benzimidazo[1,2- a ]-1,3,5-triazine, 18 phenothiazines, 19 and heteroaromatic-fused indoles. 20 In continuation of our interest in utilizing ammonium salts to synthesize N-heterocycles under metal-free conditions, herein we report a novel strategy for the formation of β-carbolines from 2-(indol-3-yl)cyclohexanones, aldehydes, and ammonium salts (Fig.…”
Section: Introductionmentioning
confidence: 99%